Status of Dermoscopy in Chile: First National Study for Dermatologists - Juan Pablo Morales Etcheberry; Francisco González-Coloma; Faustino Alonso-Traviesa; Nadia Vega-Almendra (Mattioli1885, 2024)
Introduction: Scientific evidence supports dermoscopy as an essential tool in dermatological diagnosis. Objectives: The objective is to know the factors that influence its use in Chilean dermatologists. Materials and Methods: Analytical cross-sectional study. An adapted version of the survey was submitted from the pan-European study by Forsea et.al. to members of the Chilean Society of Dermatology, between September and December 2020. Analysis using descriptive statistics and multivariate analysis with ordinal logistic regression looking for factors associated with greater use of. Results: 198 responses, mean age 46.3 years and 14.6 years on average practicing as dermatologists. 61.6% trained in dermoscopy during their residency. 98% use a dermatoscope. More than 80% consider dermoscopy useful for the diagnosis of melanomas, follow-up of melanocytic lesions, and diagnosis of pigmented and non-pigmented tumors. Between 50% and 70% consider it useful for monitoring non-melanocytic lesions, nail and hair pathologies. Greater confidence when evaluating pigmented and non-pigmented tumors and capillary pathology. Adjusting for age, sex, confidence, and education, participation in teaching was associated with greater use of dermoscopy in non-pigmented and pigmented tumors, and capillary pathology. Conclusions: Percentage of participation in the survey and training in dermoscopy higher than in the reference study, recognizing the usefulness of dermoscopy for the diagnosis and follow-up of tumor pathologies. Participating in teaching is a strong independent factor that is associated with a greater use of dermoscopy in Chile. Dermoscopy is positioned as a tool widely used by Chilean dermatologists in their daily practice.